Comparison of core antigen (p24) assay and reverse transcriptase activity for detection of human immunodeficiency virus type 1 replication. - Land, S (1989)
This report compares two assay systems for monitoring human immunodeficiency virus (HIV) replication in peripheral blood leukocyte cultures. A commercial enzyme-linked immunoassay detected core antigen (p24) in 80% of cell cultures from HIV-seropositive individuals, whereas 67% of the cell cultures produced detectable levels of reverse transcriptase activity. There were clearly three patterns of reverse transcriptase activity produced, two of which may evade detection without regular sampling and maintaining cell cultures for more than 4 weeks. Once established, core antigen levels remained high so that cell cultures could be confidently monitored by an intermittent screening regimen.